Keanekaragaman Predator Kumbang Tanah pada Area Alih Fungsi Lahan Kakao-Tebu - Alifia Cahya Safitri; Nanang Tri Tri Haryadi (Agrotechnology Research Journal, 2023)
The activity of changing land functions from rubber and cocoa plantations to sugar cane plantations and using conventional technical land processing systems can affect the population of ground surface insects such as ground beetles. Ground beetles are one of the important insects that act as predators and are sensitive to environmental conditions. The aim of this research is to determine the diversity and number of ground beetle populations in the sugar cane fields at PTPN XII Kalitelepak Plantation. This research used a pitfall trap consisting of 5 plots and 9 traps were installed in each plot with a distance of 10 m between traps. Samples were taken 15 times every 3 days. The research results showed that the ground beetles caught were from the Carabidae family which consists of the species Chlaenius bimaculatus, Chlaienius virgulifer, Chlaenius pictus, Chlaenius cambodiensis, Pheropsophus occipitalis, Pterostichus melanarius, Harpalus affinis, Nebria brevicollis, Planetes puncticeps with a total of 143 individuals. The highest important value index is the species Chlaenius bimaculatus at 104.96. The diversity of ground beetles in sugar cane plants at PTPN XII Kalitelepak Plantation is in the low category because it is less than (<) 1, namely with a value of 0.79. Human activities such as taking grass and changing land use can affect diversity, so conservation needs to be carried out to increase the diversity of ground beetles.